Role of Surface-Exposed Loops of Haemophilus influenzae Protein P2 in the Mitogen-Activated Protein Kinase Cascade - Galdiero, Stefania (American Society for Microbiology, 2003)
The outer membrane of gram-negative bacteria contains several proteins, and some of these proteins, the porins, have numerous biological functions in the interaction with the host; porins are involved in the activation of signal transduction pathways and, in particular, in the activation of the Raf/MEK1-MEK2/mitogen-activated protein kinase (MAPK) cascade. The P2 porin is the most abundant outer membrane protein of Haemophilus influenzae type b. A three-dimensional structural model for P2 was constructed based on the crystal structures of Klebsiella pneumoniae OmpK36 and Escherichia coli PhoE and OmpF. The protein was readily assembled into the β-barrel fold characteristic of porins, despite the low sequence identity with the template proteins. The model provides information on the structural features of P2 and insights relevant for prediction of domains corresponding to surface-exposed loops, which could be involved in the activation of signal transduction pathways. To identify the role of surface-exposed loops, a set of synthetic peptides were synthesized according to the proposed model and were assayed for MEK1-MEK2/MAPK pathway activation. Our results show that synthetic peptides corresponding to surface loops of protein P2 are able to activate the MEK1-MEK2/MAPK pathways like the entire protein, while peptides modeled on internal β strands are unable to induce significant phosphorylation of the MEK1-MEK2/MAPK pathways. In particular, the peptides corresponding to loops L5 (Lys206 to Gly219), L6B (Ser239 to Lys253), and L7 (Thr280 to Lys287) activate, as the whole protein, essentially JNK and p38.